Penerapan Media Gambar terhadap pembelajaran Kosa Kata bahasa Inggris dasar pada siswa kelas V SD 268 Mallahae - Kaharuddin, A.Husnul Khatimah; Sapriadi, Sapriadi (LP2M Universitas Islam Ahmad Dahlan, 2023)
The implementation of this community service is to develop human resources in Mallahae Village, Kajuara District. This program is important to be implemented among children or beginner students in learning English vocabulary using picture media. Learning English vocabulary is a first for students at SDN 258 Mallahae, so teachers need to provide interesting and varied learning media. The method implemented in the classroom is the picture method combined with several other methods according to the needs of the class and according to the material provided. The method is effective and makes students' enthusiasm increase. In addition, student attendance at school is almost 90% present in every English learning process. This indicates that students have high enthusiasm for language learning.